The Pursuit of Legal Harmony in the Integration of Sharia Economic Law Compilation, OJK Regulations, and DSN-MUI Fatwas - Tarmidzi; Khasanah, Karimatul; Arwani, Agus; Said, Kholil; Ramadhan, Mahendra Utama Cahya (Hikmatuna : Journal for Integrative Islamic Studies, 2024)
The present study aims to explore the depth of conflict of legal norms between the Sharia Economic Law Compilation (KHES), Financial Authority Services (OJK) regulations, and the National Sharia Board of the Indonesian Ulema Council (DSN-MUI) fatwas, investigate the causes of this normative divergence, and explore harmonization strategies to create legal certainty for Sharia financial institutions in Indonesia. Designed with normative legal research methodology, this study garnered data through literature review and analyzes it using interpretation method. Study findings demonstrate that there are eighteen different norms in the three regulations, with some differences resulting in conflict. The causes of these conflicts vary, including the use of ambiguous terms, adoption of conventional definitions, errors in translation of terms, and inconsistencies in concept development. In addition, the concurrent application of rules, differences in terminology, time gaps in issuance, and overlapping authorities also contribute to disharmony. This research contributes by offering a comprehensive solution, which includes identifying the sources of disharmony, harmonizing concepts and definitions, and applying legal interpretation and construction methods. This approach addresses the discrepancies and create a harmonious normative balance in policy and regulation. The implications of this research are very significant for Sharia financial institutions in Indonesia, as it identifies conflicts of legal norms between KHES, OJK regulations, and DSN-MUI fatwas and explores harmonization strategies